Recognized Obstructive Sleep Apnea is Associated With Improved In‐Hospital Outcomes After ST Elevation Myocardial Infarction - Mohananey, Divyanshu (J Am Heart Assoc, 2017)
BACKGROUND: Obstructive sleep apnea (OSA) is an independent risk factor for many cardiovascular conditions such as coronary artery disease, myocardial infarction, systemic hypertension, pulmonary hypertension, and stroke. However, the association of OSA with outcomes in patients hospitalized for ST‐elevation myocardial infarction remains controversial. METHODS AND RESULTS: We used the nation‐wide inpatient sample between 2003 and 2011 to identify patients with a primary discharge diagnosis of ST‐elevation myocardial infarction and then used the International Classification of Diseases, Clinical Modification code 327.23 to identify a group of patients with OSA. The primary outcome of interest was in‐hospital mortality, and secondary outcomes were in‐hospital cardiac arrest, length of stay and hospital charges. Our cohort included 1 850 625 patients with ST‐elevation myocardial infarction, of which 1.3% (24 623) had documented OSA. OSA patients were younger and more likely to be male, smokers, and have chronic pulmonary disease, depression, hypertension, known history of coronary artery disease, dyslipidemia, obesity, and renal failure (P<0.001 for all). Patients with OSA had significantly decreased in‐hospital mortality (adjusted odds ratio, 0.78 [95% CI, 0.73–0.84]), longer hospital stay (5.00±4.68 versus 4.85±5.96 days), and incurred greater hospital charges ($79 460.12±70 621.91 versus $62 889.91±69 124.15). There was no difference in incidence of in‐hospital cardiac arrest (adjusted odds ratio, 0.93 [95% CI, 0.84–1.03]) between these 2 groups. CONCLUSION: ST‐elevation myocardial infarction patients with recognized OSA had significantly decreased mortality compared with patients without OSA. Although patients with OSA had longer hospital stays and incurred greater hospital charges, there was no difference in incidence of in‐hospital cardiac arrest.